2009
DOI: 10.1302/0301-620x.91b12.22481
|View full text |Cite
|
Sign up to set email alerts
|

The level of vitamin D in the serum correlates with fatty degeneration of the muscles of the rotator cuff

Abstract: This study examined the role of vitamin D as a factor accounting for fatty degeneration and muscle function in the rotator cuff. There were 366 patients with disorders of the shoulder. A total of 228 patients had a full-thickness tear (group 1) and 138 patients had no tear (group 2). All underwent magnetic resonance arthrography and an isokinetic muscle performance test. The serum concentrations of vitamin D (25(OH)D(3)) were measured. In general, a lower serum level of vitamin D was related to higher fatty de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
78
1
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(82 citation statements)
references
References 42 publications
0
78
1
3
Order By: Relevance
“…21 In addition, two studies reported an association between low 25(OH)D levels and fatty degeneration of thigh and rotator cuff muscles. 23,24 This potential effect of vitamin D on muscle biology is likely to affect creatinine production. Indeed, an increase in creatininemia due to enhanced creatinine production without variation in GFR has been reported under calcitriol therapy.…”
Section: Discussionmentioning
confidence: 99%
“…21 In addition, two studies reported an association between low 25(OH)D levels and fatty degeneration of thigh and rotator cuff muscles. 23,24 This potential effect of vitamin D on muscle biology is likely to affect creatinine production. Indeed, an increase in creatininemia due to enhanced creatinine production without variation in GFR has been reported under calcitriol therapy.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been implicated in the risk of overall mortality [26], cancer [19,21,26], diabetes [21,26], musculoskeletal disorders [16,26], hypertension [21,26], heart disease [21,26], multiple sclerosis [19], stroke [21], and even falls [4,8,20]. Recent epidemiologic data suggest a widespread deficiency of vitamin D [13,18].…”
Section: Introductionmentioning
confidence: 99%
“…There are substances that have an anabolic effect on muscle and could potentially counteract the formation of interfiber gaps induced by atrophy, which are known to be filled with fat. Several pharmacological substances influence the development, growth, and repair mechanisms of muscle, namely, anabolic steroids [11][12][13][14][15][16][17][18][19][20] , growth hormones [21][22][23][24] , b-2 agonists, heparan sulfate 25 , xanthine derivatives 26 , creatine 27 , and vitamin D 28 . Of all of these substances, anabolic steroids seem best suited for clinical application.…”
mentioning
confidence: 99%